STRUCTURE AND FUNCTION OF E. coli RIBOSOMES, VIII. COLD-SENSITIVE MUTANTS DEFECTIVE IN RIBOSOME ASSEMBLY - Guthrie, Christine (1969)
E. coli mutants that fail to grow at 20°C were isolated, and three such mutants were studied in detail. Two of these are defective in 50S ribosome biosynthesis at low temperatures and accumulate 43S and 32S particles, respectively. The third mutant produces reduced amounts of 50S ribosomes and accumulates 21S particles at low temperatures. The 43S and 32S particles contain 23S RNA and appear to be precursors of 50S ribosomes. The 21S particles contain 16S RNA. The mutation that causes accumulation of 32S particles is linked to the spc locus. Isolation and characterization of coldsensitive mutants should provide a fruitful approach to the study of in vivo ribosomal assembly.